2004
DOI: 10.1074/mcp.m400054-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput Functional Genomics Identifies Genes That Ameliorate Toxicity Due to Oxidative Stress in Neuronal HT-22 Cells

Abstract: We describe a novel genetic screen that is performed by transfecting every individual clone of an expression clone collection into a separate population of cells in a highthroughput mode. We combined high-throughput functional genomics with experimental validation to discover human genes that ameliorate cytotoxic responses of neuronal HT-22 cells upon exposure to oxidative stress. A collection of 5,000 human cDNAs in mammalian expression vectors were individually transfected into HT-22 cells, which were then e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…GFPT2 is known to reduce peroxide toxicity associated with oxidative stress (Zitzler et al 2004). TF is implicated in iron transport that is positively related to oxidative stress (conversion of peroxide to OH.)…”
Section: Gene Analysismentioning
confidence: 99%
“…GFPT2 is known to reduce peroxide toxicity associated with oxidative stress (Zitzler et al 2004). TF is implicated in iron transport that is positively related to oxidative stress (conversion of peroxide to OH.)…”
Section: Gene Analysismentioning
confidence: 99%
“…Previously, it was reported that peroxiredoxin 1 and 5 have been shown to ameliorate ROS-induced cytotoxicity (18). These results clearly showed that the defense system involving antioxidant enzymes against oxidative stress is activated by glutamate-induced stress.…”
Section: Resultsmentioning
confidence: 64%
“…HSP70 is known to inhibit apoptosis by neutralizing and interacting with AIF (36). Overexpression of HSP70 also ameliorates glutamate-induced cell death in HT22 cells (18). More extensive studies are needed to elucidate whether HSP70 interacts with AIF or if AIF has certain functional roles in glutamate-induced cell death.…”
Section: Post-translational Modification and Subcellular Translocationmentioning
confidence: 99%
“…15,16 The pipeline (Fig. 1a) begins with individual cDNA expression plasmids from which are propagated (by Robot 1) in bacteria and isolated by a high throughput Robot 2 (20,000 preps per 24 hr) that delivers reproducible quantities of plasmids without contaminations that interfere with subsequent transfection assays.…”
Section: Resultsmentioning
confidence: 99%
“…For this, we have developed a robotics platform, which performs high throughput transfection of single cDNAs into mammalian cells, followed by determination of cellular phenotypes such as proliferation and cell death. 15,16 Because the balance between proliferation and apoptosis is crucial for normal development and homeostasis, 17,18 genes or genetic alterations that interfere with this balance cause diseases, e.g., cancer. 8,9 Our expression and phenotype-determination platform can mimic gain of function deregulation and analyze the resulting phenotype.…”
mentioning
confidence: 99%